Control of the Elastic Torsion System based on Dynamic Matrix Control Algorithm - Jiang Hao; Yu Songzhou (Jixie chuandong)
The multi-mass elastic torsional system has the feature of large speed fluctuation and long vibration time.The system state space model is built based on the system analysis,and the parameters of this model are estimated by using Simulink Parameter Estimation Toolbox.The system speed is controlled by using dynamic matrix control（DMC）algorithm.The DMC controller is converted into embedded C code which is executable for PLC by using Simulink Coder toolbox in Matlab.After being compiled by Automation Studio,it will be downloaded to X20 PLC to control the real system.Both the simulation and practical system test shows that the model is accurate and DMC algorithm is better than cascade PID algorithm in dynamic performance.